Properties of gliricidia wood (Gliricidia sepium) intercropped with cocoa (Theobroma cocoa) in Malaysia / Mohd Helmy Ibrahim, Mohd Nazip Suratman and Razali Abd Kader - Ibrahim, Mohd Helmy; Suratman, Mohd Nazip; Abd Kader, Razali (Research Management Institute (RMI), 2014)
Trees planted from agroforestry practices can become valuable resources in meeting the wood requirements of many nations. Gliricidia sepium is an exotic species introduced to the agricultural sector in Malaysia mainly for providing shade for cocoa and coffee plantations. This study investigates its wood physical properties (specific gravity and moisture content) and fibre morphology (length, lumen diameter and cell wall thickness) of G.sepium at three intervals according to age groups (three, five and seven years of ages). Specific gravity (0.72) was significantly higher at seven years of age as compared to five (0.41) and three (0.35) years age group with a mean of 0.43 (p0.05). Mean moisture content was 58.3 % with no significant difference existing between the tree age groups. fibre diameter (22.4 m) was significantly lower (p0.05) for the trees which were three years of age when compared to five and seven years age groups (26.6 m and 24.7 m), respectively. Means of fibre length, lumen diameter and cell wall thickness was 0.83 m, 18.3 m, and 6.2 m, respectively, with no significant differences detected between trees in all age groups in this study. Further calculation on the coefficient of suppleness and runkel ratio suggest that wood from G. sepium may have the potential for insulation board manufacture and paper making. However, future studies should experiment the utilization of this species for these products to determine its full potential.